Evaluation of a system for segmental speech quality assessment: Voiceless fricavties. - Wrench, Alan; Jackson, M S; Soutar, D S; Robertson, A G; Beck, J Mackenzie (International Speech Communication Association, 1995)
In this paper, an automatic assessment procedure for monitoring the speech progress of patients who have undergone intra-oral surgery is evaluated. The metric is currently limited to fricative segments and is based on centroid analysis of the speech spectra. The scores provided by this means are correlated with an articulatory assessment provided by a panel of 3 phoneticians. Preliminary results show a degree of correlation between mean panel scores for perceived quality and scores relating to this measure obtained by computer analysis but lateral and nasal co-articulation are not well represented by the metric.
Keywords: intra-oral surgery; speech